2016
DOI: 10.1016/j.socec.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

To trust, or not to trust: Cognitive reflection in trust games

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
0
30
0
2
Order By: Relevance
“…Because trust is cognitive (Corgnet et al . ), these determinants are important; they show that they are significant in every model even when more institutional variables are added. Attesting to the present study, a study by Foster (1965) also confirmed that the daily struggle and the feeling of insecurity within a society negatively affect trust.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Because trust is cognitive (Corgnet et al . ), these determinants are important; they show that they are significant in every model even when more institutional variables are added. Attesting to the present study, a study by Foster (1965) also confirmed that the daily struggle and the feeling of insecurity within a society negatively affect trust.…”
Section: Resultsmentioning
confidence: 91%
“…Individuals react based on their belief or knowledge of others. A member of one sect may have a personal reason to distrust an individual from another sect; this distrust is then reflected on all members of that sect (Corgnet et al 2014). Subsequently, others will react to his distrust with distrust.…”
Section: What Is Generalised Trust?mentioning
confidence: 99%
“…They include the amount the trustor expects to receive in return, social preferences toward ingroups and out-groups, risk attitudes, and gender. We include the performance in the math quiz as a proxy for higher intellectual abilities, because previous studies have suggested that more intelligent people trust more (e.g., Corgnet et al, 2016). We add a dummy variable indicating that the trustor somewhat or strongly disagrees with the statement about the importance of math skills, as it could capture a negative perception of the legitimacy of the selection of experts.…”
Section: Behavior Of the Upwardly Mobile Individualsmentioning
confidence: 99%
“…Additionally, players with higher cognitive abilities reciprocated cooperation in the second round of this PDG significantly more than low intelligent subjects. Specifically, in a series of incentivized trust games, Corgnet et al (2015) showed that cognitive ability is positively correlated to trust but not with trustworthy behavior. Thus, individuals’ cognitive ability/intelligence has been associated with cooperative play in economic games.…”
Section: Introductionmentioning
confidence: 99%